A new look on CSI imperfection in downlink NOMA systems - Anh-Tu Le; Dinh-Thuan Do (Bulletin of Electrical Engineering and Informatics, 2021)
Observing that cooperative scheme benefits to non-orthogonal multiple access (NOMA) systems, we focus on system performance analysis of downlink. However, spectrum efficiency is still high priority to be addressed in existing systems and hence this paper presents full-duplex enabling in NOMA systems. Other challenge needs be considered related to channel state information (CSI). In particular, we derive closedform expressions of outage probability for such NOMA systems under the presence of CSI imperfection. Furthermore, to fully exploit practical environment, we provide system model associated with Nakagami-m fading. The Monte-Carlo simulations are conducted to verify the exactness of considered systems.